Amorphous structure and sulfur doping synergistically inducing defect-rich short carbon nanotubes as a superior anode material in lithium-ion batteries. (1st February 2023) - Li, Xiying; Xue, Chunjian; Liu, Yinpeng; Zhao, Jinlian; Zhang, Jiwei; Zhang, Jingwei
Highlights: Short amorphous carbon nanotubes (SACTs) with a hierarchical pore structure is fabricated. Defect-rich structures are induced synergistically by sulfur doping and the amorphous nature of SACTs Defects endow the sulfur-doped SACTs with additional active sites and improve diffusion kinetics of Li ions. Sulfur-doped SACTs features excellent high-rate capacity and cycling performance. Abstract: Carbon anode materials have slow electron ion transport kinetics, which present challenges to the further practical application for lithium-ion batteries (LIBs). The morphology, crystallinity and defect structure of carbonaceous materials play crucial roles in the performance of LIBs. Herein, a defect-rich and sulfur-doped short amorphous carbon nanotubes (SACTs-S) with a hierarchical pore structure is reported and demonstrate their potential anode material in high-performance LIBs. Defect-rich structures are induced synergistically by sulfur doping and the amorphous nature of short amorphous carbon nanotubes. These defects not only endow the SACTs-S with additional active adsorption sites and good electrolyte/electrode interfacial compatibility but also improve diffusion kinetics of Li ions, thereby reducing Li ions migration barriers. These beneficial characteristics enabled the SACTs-S a high reversible capacity of 1608.7 mA h g −1 at 50 mA g −1 and an excellent cycle stability of 538.0 mA h g −1 over 2500 cycles at 2000 mA g −1 . Also, the first-principle calculations reveal that additional defects created by sulfur doping can favor Li ions adsorption, conductivity enhancement and the reduction in Li ions diffusion barrier. This work thus presents an effective strategy for designing superior electrode materials for LIBs. Graphical abstract: Image, graphical abstract